2020
DOI: 10.1016/j.molcel.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The Configuration of RPA, RAD51, and DMC1 Binding in Meiosis Reveals the Nature of Critical Recombination Intermediates

Abstract: Summary Meiotic recombination proceeds via binding of RPA, RAD51, and DMC1 to single-stranded DNA (ssDNA) substrates created after formation of programmed DNA double-strand breaks. Here we report high-resolution in vivo maps of RPA and RAD51 in meiosis, mapping their binding locations and lifespans to individual homologous chromosomes using a genetically engineered hybrid mouse. Together with high-resolution microscopy and DMC1 binding maps, we show that DMC1 and RAD51 have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 72 publications
(205 reference statements)
9
154
0
3
Order By: Relevance
“…Additionally, we note that genomic positions of DSBs and cohesin ChIP sites appear to have relatively low cis/total ratios, despite the fact that immunofluorescent microscopy shows DSB machinery and cohesin subunits enriched along the axes [47,48,49]. In general, genomic loci with axial positions in a brush-loop structure would be expected to display high cis/total ratios characteristic of low spatial accessibility.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, we note that genomic positions of DSBs and cohesin ChIP sites appear to have relatively low cis/total ratios, despite the fact that immunofluorescent microscopy shows DSB machinery and cohesin subunits enriched along the axes [47,48,49]. In general, genomic loci with axial positions in a brush-loop structure would be expected to display high cis/total ratios characteristic of low spatial accessibility.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the Hi-C signals we observe at DSB or crossoverfavoured genomic coordinates are unlikely to directly reflect chromosomal configuration at individual DSB and crossover events, as even the most favoured coordinates are not sites of recombination in most cells. Additionally, we note that genomic positions of DSBs and cohesin ChIP sites appear to have relatively low cis/total ratios, despite the fact that immunofluorescent microscopy shows DSB machinery and cohesin subunits enriched along the axes [47, 48, 49]. In general, genomic loci with axial positions in a brush-loop structure would be expected to display high cis/total ratios characteristic of low spatial accessibility.…”
Section: Discussionmentioning
confidence: 95%
“…This massive induction of DNA DSBs, of course, requires an efficient repair mechanism. Following the exchange of genetic material between homologous chromosomes, lesions are repaired by the homologous recombination (HR) pathway that is dependent on DMC1 and RAD51 [18]. Approximately 10% of the lesions are thus repaired by a crossover and 90% by a non-crossover mechanism.…”
Section: Double-strand Break Checkpointmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) sequencing (ChIP-seq) was one of the earlier methods to incorporate NGS and has been applied in order to identify sites of protein-DNA interactions [86]. Work done by Hinch et al demonstrated the use of ChIP-seq in order to understand the roles of RPA, RAD51 and DMC1 in the strand exchange of mammalian meiosis [87]. ChIP-seq can also be utilized to study the chromatin state of genes, by immunoprecipitating and analyzing epigenetic modifications, as demonstrated by Grosselin et al [88].…”
Section: Mapping Of Dsbs By Next Generation Sequencingmentioning
confidence: 99%
“…Work done by Hinch et al demonstrated the use of ChIP-seq in order to understand the roles of RPA, RAD51 and DMC1 in the strand exchange of mammalian meiosis [87]. ChIP-seq can also be utilized to study the chromatin state of genes, by immunoprecipitating and analyzing epigenetic modifications, as demonstrated by Grosselin et al [88].…”
Section: Cells 2020 9 X For Peer Review 7 Of 19mentioning
confidence: 99%